2013
DOI: 10.1155/2013/848363
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Pachymetry Using Spectral-Domain Optical Coherence Tomography during Accelerated Corneal Collagen Crosslinking

Abstract: Purpose. To evaluate the role of spectral-domain optical coherence tomography (SDOCT) to measure corneal thickness during accelerated corneal crosslinking (CXL). Methods. Intraoperative pachymetry was performed using SDOCT and ultrasound pachymetry (USP) in 6 eyes of 6 patients with keratoconus. Pachymetry readings were obtained at baseline, after epithelium removal and after 30 minutes of riboflavin instillation. SDOCT measurements of eyes with and without lid speculum during riboflavin instillation were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Other studies8 evidenced the limited use of hypotonic riboflavin solutions that transiently increased intraoperative corneal pachymetry, although the final thinnest point remained unchanged, and concluded that to increase endothelial safety, new iso-oncotic solutions would be necessary 9. Some authors proposed the transepithelial CXL that, according to its limited penetration, seemed more indicated for patients with thin corneas 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies8 evidenced the limited use of hypotonic riboflavin solutions that transiently increased intraoperative corneal pachymetry, although the final thinnest point remained unchanged, and concluded that to increase endothelial safety, new iso-oncotic solutions would be necessary 9. Some authors proposed the transepithelial CXL that, according to its limited penetration, seemed more indicated for patients with thin corneas 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…Our study results are also in agreement with previous studies using OCT for pachymetry measurements during CXL. Mazzotta et al 7 reported a reduction of 144.43 μm (32.1%) in CTP measurements when an eyelid speculum was left in place; with the majority of the stromal shrinkage occurring in the first 10 min of the riboflavin instillation, Chow et al 11 in their study of six eyes of six patients observed a 126 μm and 66 μm decrease in the CPT measurements in patients with and without lid speculum, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, previous studies point have noted the significant role played by corneal exposure during the imbibition period, which is one factor that induces corneal shrinkage within the presence of the standard isotonic riboflavin-dextran solution and epithelium-off CXL, when an eyelid speculum is left in place. [10][11][12] In addition, the subsequent treatment duration over which the cornea remains exposed could also potentially affect the final pachymetry.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative corneal thickness can be measured with ultrasound pachymetry or optical coherence tomography. 6 At the end of the irradiation process, a broad-spectrum antibiotic drop is instilled on the cornea, followed by the placement of a bandage contact lens. Topical corticosteroids can be used to reduce postoperative inflammation or corneal haze.…”
Section: Surgical Procedures Of Corneal Collagen Cross-linkingmentioning
confidence: 99%